Controllable inter-line bonding performance and fracture patterns of continuous fiber reinforced composites by sinusoidal-path 3D printing. (26th May 2020) - Shang, Junfan; Tian, Xiaoyong; Luo, Meng; Zhu, Weijun; Li, Dichen; Qin, Yingjie; Shan, Zhongde
Abstract: In order to improve the inter-line bonding performance of 3D printed continuous fiber reinforced composites, an innovative sinusoidal-path extrusion 3D printing method was proposed. Conventional 3D printing constructs components from stacks of individual extruded straight lines and flat layers, resulting in the relatively weak bonding that occurs between individual lines and layers and is aggravated due to the introduction of continuous fibers. The influence of structural parameters (amplitude & frequency) on the inter-line tensile properties and fracture patterns of sinusoidally 3D printed composites were systematically investigated. The results showed that as the amplitude and frequency of the sinusoidal path increased, the inter-line tensile strength, tensile modulus and fracture energy absorption of CCF/PLA composites increased 95.4%, 57.3% and 165%, respectively. Based on this study, a non-planar sinusoidal layer extrusion 3D printing method of CFRTPCs was proposed, which provides a new idea for comprehensive control of the anisotropy of 3D printed composites.